Abnormal chirality in antiferromagnetic resonance modes of van der Waals 2D magnets - Chao Chen; Cuixiu Zheng; Shanshan Hu; Hao-Hsuan Chen; Jianwei Zhang; Yaowen Liu (Scientific Reports)
Abstract Two-dimensional van der Waals (2D vdW) materials have attracted widespread research interest due to their unique physical properties and potential application prospects. In this study, an atomistic-level dynamical simulation method is employed to investigate the chirality of antiferromagnetic resonance modes in CrI3 bilayer. Beyond the typical observations of a linear increase in high-frequency resonance mode and a linear decrease in low-frequency resonance mode, we have identified a distinct magnetization precession chirality in the CrI3 bilayer at low magnetic fields: Spins in different layers exhibit opposite precession chirality. This unusual chirality phenomenon is attributed to the weak interlayer coupling inherent in vdW materials, which can be adjusted by tuning their interlayer coupling and perpendicular magnetic anisotropy. These findings provide valuable insights into the intrinsic antiferromagnetic resonance characteristics of atomically thin vdW materials and their potential implications for the development of spintronic devices.